PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DAN PEMBANGUNAN PARIWISATA PANTAI PULISAN DI DESA PULISAN KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Patadungan, Ellyn; Tasik, Femmy; Purwanto, Antonius (Sam Ratulangi University, 2022)
This study aims to determine community participation in the development and development of Pulisan Beach tourism in Pulisan Village, East Likupang District, North Minahasa Regency, North Sulawesi Province. This research was conducted from November to December 2021. This type of research used a descriptive qualitative method. The results showed that the development of the Pulisan Beach tourism object in Pulisan Village had involved many parties such as the village government, community leaders, and the entire community. Participation in the implementation of activities in this research is a continuation of the decision-making that has been mutually agreed upon during the deliberation in its implementation which is planned by the government to influence the success of a tourism development process. Furthermore, the Pulisan Village government in an evaluation meeting related to the implementation of the program as a whole has never been carried out with the community in Pulisan Village in the development of Pulisan Beach tourism. Participation in the utilization of the results found that there was data showing an increase in the number of tourists visiting Pulisan beach tourism objects in 2018 to 2019 after tourism development carried out by the government and the community.